MABS: Spreadsheet– based decision support for precision marketing - DE REYCK, Bert (Institutional Knowledge at Singapore Management University, 2006)
In this paper, we describe a decision support system developed for automatically scheduling and optimising broadcasts of advertisements to mobile phones via SMS (Short Message Service) text messaging. The system, MABS or “Mobile Advertising Broadcast Scheduler”, is developed in Microsoft Excel with a link to Lingo, a modelling language and IP solver. It was developed for a London-based company specialized in location-sensitive precision marketing via mobile phones. The system significantly reduced the time required to schedule the broadcasts, and resulted both in increased customer response and revenues.